An overview of the cultivation and commercialization of the caterpillar fungus, Ophiocordyceps sinensis sited in the Tibetan Plateau and the Himalayan forests of Bhutan and Nepal - Norliana, Munir; Aizi Nor Mazila, Ramli; Bhuyar, Prakash; Nur Izyan, Wan Azelee (Biodiversity Conservation Society, 2023)
Ophiocordyceps sinensis is a unique entomopathogenic fungus and valuable Chinese medicine resource that has been employed for treating various human conditions. Limited O. sinensis in the wild due to over-exploitation has led it to the brink of extinction. This caused a massive disparity between supply and demand, resulting in skyrocketing prices. The dumping of counterfeit products in the market also caused the need for quality control. In this review, effort has been made to understand the development of O. sinensis and its life cycle, in which the possible cultivation method can be discussed. Additionally, it also summarizes the analytical method for quality control measures in order to ensure the quality of artificially cultivated O. sinensis are on par or even better than the wild. Furthermore, the commercialization of artificially cultivated Cordyceps is lightly touched. Despite these challenges, research into the cultivation of Ophiocordyceps sinensis continues, as it has the potential to provide a sustainable source of the fungus for medicinal purposes. Some pharmaceutical companies have already developed products containing Ophiocordyceps sinensis, and further research may lead to the discovery of new therapeutic applications for the fungus. However, it is important to ensure that the cultivation and commercialization of Ophiocordyceps sinensis is done in an ethical and sustainable manner, to avoid further depletion of the wild populations of the fungus.